Analysis Of Factors Affecting Interest Kai Access Application Users Using Models Unified Theory Of Acceptance And Use Of Technology 2 (UTAUT 2) - Firmansyah, Rifki; Fauziah, Yuli; Perwira, Rifki Indra (Telematika, 2023)
Purpose: This study aims to analyze the factors that influence user interest in the KAI Access application using the Unified Theory Of Acceptance And Use Of Technology 2 (UTAUT 2) model.Methodology: This study used the Structural Equation Modeling (SEM) method with two tests, namely the outer model and the inner model with the help of the SmartPLS Version 3 software. A total of 406 respondent data were used from the Special Region of Yogyakarta and also users of the KAI Access application.Results:  The results of the study show that of the fourteen hypotheses proposed in the study, only seven were accepted, namely social influence, facilitating conditions, hedonic motivation, price value, and habit. The strongest factors that have a significant effect are hedonic motivation and habit.State of the art: based on previous research, this study has quite similar characteristics but different cases, variables, and research samples.